2018
DOI: 10.1016/j.ajhg.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Argininosuccinate Lyase Deficiency Causes an Endothelial-Dependent Form of Hypertension

Abstract: Primary hypertension is a major risk factor for ischemic heart disease, stroke, and chronic kidney disease. Insights obtained from the study of rare Mendelian forms of hypertension have been invaluable in elucidating the mechanisms causing primary hypertension and development of antihypertensive therapies. Endothelial cells play a key role in the regulation of blood pressure; however, a Mendelian form of hypertension that is primarily due to endothelial dysfunction has not yet been described. Here, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 44 publications
(57 reference statements)
3
61
0
Order By: Relevance
“…As LC is critically involved in orchestrating the central stress responses involving cardiovascular and stereotypical manifestations (Elam et al., 1984, Ogawa et al., 1977, Saran et al., 1978), we wanted to explore whether LC loss of ASL could contribute to the hypertension observed in mice and humans with ASLD. Using continuous blood pressure telemetric measurements, and consistent with our previous reports, we found that endothelial-ASL cKO mice ( Asl f/f ;Cdn Cre +/− ) have a significantly higher blood pressure (Kho et al., 2018). In contrast, LC-ASL cKO mice ( Asl f/f ;TH Cre +/− ) demonstrated blood pressure and heart rate that were comparable to their control littermates (Figures S4C and S4D).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As LC is critically involved in orchestrating the central stress responses involving cardiovascular and stereotypical manifestations (Elam et al., 1984, Ogawa et al., 1977, Saran et al., 1978), we wanted to explore whether LC loss of ASL could contribute to the hypertension observed in mice and humans with ASLD. Using continuous blood pressure telemetric measurements, and consistent with our previous reports, we found that endothelial-ASL cKO mice ( Asl f/f ;Cdn Cre +/− ) have a significantly higher blood pressure (Kho et al., 2018). In contrast, LC-ASL cKO mice ( Asl f/f ;TH Cre +/− ) demonstrated blood pressure and heart rate that were comparable to their control littermates (Figures S4C and S4D).…”
Section: Resultssupporting
confidence: 91%
“…This is best illustrated by the complex phenotype observed in individuals with argininosuccinic aciduria or ASL deficiency (ASLD), a urea cycle disorder that is caused by germline, loss-of-function, pathogenic variants in ASL (Baruteau et al., 2017, Erez et al., 2011a, Mercimek-Mahmutoglu et al., 2010, Nagamani et al., 2011, Nagamani et al., 2012b, Tuchman et al., 2008). In spite of having fewer episodes of hyperammonemia as compared to individuals with other urea cycle disorders (UCDs), individuals with ASLD are at increased risk to develop intellectual and learning disabilities, behavioral abnormalities, epilepsy, ataxia, and hypertension (Baruteau et al., 2018, Brunetti-Pierri et al., 2009, Ficicioglu et al., 2009, Kho et al., 2018, Kleijer et al., 2002, Lågas and Ruokonen, 1991, Tuchman et al., 2000). Thus, pathogenic mechanisms other than hyperammonemia likely contribute to the phenotypes observed in ASLD.…”
Section: Introductionmentioning
confidence: 99%
“…Other clinical features of the disorder may include trichorrhexis nodosa, cognitive impairment, seizures, hypokalemia, diarrhea, and liver disease (4). Systemic hypertension has also been described in a subset of individuals with ASLD (3,(5)(6)(7)(8). Treatment typically includes low-protein diet with essential amino acid supplementation, arginine supplementation, use of nitrogen-scavenging agents, and -in some cases -liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ASA is a complex multifactorial disease, not only affecting the functioning of the urea cycle but also other pathways, which are probably responsible for the many other clinical manifestations seen besides hyperammonaemia—such as mental delay, epilepsy, liver fibrosis and cirrhosis and hypertension‐ even if the patients were successfully treated from the neonatal age . These manifestations are not reported for the other UCD disorders.…”
Section: Discussionmentioning
confidence: 99%